Altered Gray Matter Volume and Its Correlation With PTSD Severity in Chinese Earthquake Survivors - Zhang, Xiaoyu; Zhang, Jianxin; Wang, Li; Zhang, Wencai (Frontiers in Psychiatry, 2018)
Objective: To detect the changes of gray matter volume (GMV) and their correlation with severity of symptom in patients with post-traumatic stress disorder (PTSD) who were defined with updated DSM-5 diagnostic criteria. Method: 71 participants were assigned into PTSD group (n=35) or trauma-exposed control (TEC) group (n=36) with the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Voxel-based morphometry analysis was used to detect alterations in GMV in the PTSD group. Results: We found that the PTSD group had larger GMV in the left middle temporal gyrus (MTG) and in the right dorsal medial prefrontal cortex (dmPFC), and smaller GMV in the region of the right temporal pole (TP) than the TEC group. We also found that PTSD Checklist for DSM-5 (PCL-5) scores correlated positively with the left MTG and right dmPFC GMV, and negatively with left TP GMV. These correlations were consistent with the findings of the between-group comparisons. Conclusions: GMV alterations in the MTG, dmPFC, and TP are detected in the group comparisons and correlated with symptom severity when classifying PTSD individuals according to DSM-5 diagnostic criteria within an earthquake-exposed population.